ARTI PENTING IDEOLOGI BAGI PARTAI POLITIK - Andriana, Nina (Jurnal Penelitian Politik, 2010)
Politicalparty has an important role in thepolitical system Itfunctions such as political recruitment politicaleducation political aggregation andpolitical socialization has been positioned on the basic structure ofdemocratic system In the reformation era almost all ofpolitical parties in Indonesia has been born accidentally withoutgoodpreparation on it Itjust becomes the expression ofpolitical elite power so then political party doesn t haveits own ideology or even identity In this sense ideology is very important as a guidefor the politicalparty actionsand as a measurementfor the voter to evaluate howfarpolitical elitefuoill their promises during campaign Thisis a book review ofFirmanzah which talked about how to manage a political party by using ideology and a goodcommunication to the constituence